Quantitative detection and correlation of Epstein - Barr Virus in plasma with gingivitis and severity of chronic periodontitis by using real-time polymerase chain reaction technique - Nada K Imran; Basima Gh Ali; Duraid Q Jassim (College of Dentistry/ University of Baghdad, 2014)
Background: The main purpose of this study is to find if there is any correlation between the level of C-reactive protein (CRP) in gingival crevicular fluid with its serum level in chronic periodontitis patients and to explore the differences between them according to the probing depth. Materials and methods: Forty seven male subjects enrolled in this study. Thirty males with chronic periodontitis considered as study group whom further subdivided according to probing depth into subgroup 1 with pocket depth ≤6mm, subgroup 2 with pocket depth >6mm. The other 17 subjects considered as controls. For all subjects, clinical examination where done for periodontal parameters plaque index (PLI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment level (CAL). The gingival crevicular fluid (GCF) were collected using filter paper size 30 from gingival sulcus of the controls and from (138) pocket site (75 sites > 6mm. and 63 ≤ 6mm.). The weight of the GCF was measured by reading the difference in the weight of filter paper before and after absorption of GCF. Crevicular level of CRP was measured calorimetrically. The serum level CRP was measured using latex test. Results: Highly significant difference in the weight of GCF, crevicular and serum level of CRP between chronic periodontitis and control groups. Subgroup 2 got higher scores of weight of GCF and positive record of crevicular and serum CRP compared with subgroup 1 with a non-significant difference. A highly significant difference in the number of sites with positive crevicular and serum CRP compared to the negative number between chronic periodontitis and control groups also between subgroup1 and subgroup 2. Weight of GCF gets a negative significant correlation with GI at control group and subgroup2. Serum level of CRP exhibits a negative significant correlation with PLI for chronic periodontitis and control group and positive significant correlation for GI at subgroup 1. The crevicular CRP get significant negative correlation with GI of subgroup 1. Conclusions: Crevicular fluid is very good marker for the degree of inflammation of the periodontal pocket. The crevicular level of CRP may be considered as a good tool for estimating the systemic effect and predictor for the effect of periodontitis on the general health and the correlation of crevicular with serum CRP aid to high light this effect.